A magyar nemzetiség önrendelkezésének lehetőségei az oktatás és kultúra területén Jugoszláviában - Lóránt, Bali (Közép-Európai Közlemények, 2021)
The self-determination of the Hungarian nationality in the state socialist Yugoslavia depended significantly on the current political processes. Following the retaliation of World War II, the mid-1970s were marked by a period of significant easing. By the early 1980s, there were encouraging signs of cultural autonomy for the special traveler in Yugoslavia. The conditions for language use, education and the enforcement of national interests have been created. Nevertheless, the number of Hungarians also decreased significantly in Vojvodina, South Baranya and the Muravidék. Not only due to assimilation pressure, but also due to emigration.